Kris019
contestada

[tex]\frac{4\sqrt{3} - 12\sqrt{5} }{2\sqrt{3}+8\sqrt{5} } * \frac{2\sqrt{3} - 8\sqrt{5} }{2\sqrt{3} - 8\sqrt{5}}[/tex]

Respuesta :

Step-by-step explanation:

-18-2√15/11

Answer:

  • [tex](2\sqrt{15}-18)/11[/tex]

Step-by-step explanation:

  • [tex](4\sqrt{3}-12\sqrt{5})/(2\sqrt{3}+8\sqrt{5})*(2\sqrt{3}-8\sqrt{5})/(2\sqrt{3}-8\sqrt{5}) =[/tex]
  • [tex](4\sqrt{3}-12\sqrt{5})(2\sqrt{3}-8\sqrt{5})/(2\sqrt{3}+8\sqrt{5})(2\sqrt{3}-8\sqrt{5})=[/tex]
  • [tex](8*3- 32\sqrt{15} -24\sqrt{15} +96*5)/(4*3-64*5)=[/tex]
  • [tex](24+480-56\sqrt{15})/(12-320)=[/tex]
  • [tex](504 - 56\sqrt{15})/(-308) =[/tex]
  • [tex](2\sqrt{15}-18)/11[/tex]